Has the privacy of student users in the libraries of Faculty of Philosophy in Zagreb been violated? - Barbarić, Ana (Array, 2003)
In October 2002 we conducted a survey of protecting student users' privacy in the libraries at the Faculty of Philosophy in Zagreb, Croatia. The survey focuses on what the users know about their personal data in the libraries. We also wanted to find out whether they thought their privacy and anonymity were jeopardized. Student users of the faculty libraries were interviewed. Results of the survey upheld our hypothesis – the student users do not know enough about their right to protection of privacy because the librarians did not introduce that right to them.